2022
DOI: 10.1155/2022/2427802
|View full text |Cite
|
Sign up to set email alerts
|

Several Alkaloids in Chinese Herbal Medicine Exert Protection in Acute Kidney Injury: Focus on Mechanism and Target Analysis

Abstract: Objectives. Acute kidney injury (AKI) is a loose set of kidney diseases accompanied by a variety of syndromes, which is a serious threat to human life and health. Some alkaloids are derived from various Chinese herbs have been widely concerned in the improvement of AKI. This review provides the research progress of alkaloids in AKI experimental models and discusses the related molecular mechanisms. Key Findings. Alkaloids can protect AKI through various mechanisms including antioxidant stress, improvement of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…These findings indicate that discovering substances that can activate the Nrf2/HO-1 axis might be one of the appropriate strategies to counteract cellular damage caused by oxidative stress. Recently, numerous studies have suggested that various natural products have antioxidant properties that can inhibit oxidative damage-mediated apoptosis in myoblasts through activation of the Nrf2/HO-1 signaling (Rui et al, 2022;Wu et al, 2022;Xu et al, 2021;Zhang et al, 2021). Therefore, we investigated whether MEMC could activate Nrf2 and found that the level of p-Nrf2 expression indicating that Nrf2 was activated was clearly upregulated by H 2 O 2 in MEMC-pretreated C2C12 cells.…”
Section: Discussionmentioning
confidence: 91%
“…These findings indicate that discovering substances that can activate the Nrf2/HO-1 axis might be one of the appropriate strategies to counteract cellular damage caused by oxidative stress. Recently, numerous studies have suggested that various natural products have antioxidant properties that can inhibit oxidative damage-mediated apoptosis in myoblasts through activation of the Nrf2/HO-1 signaling (Rui et al, 2022;Wu et al, 2022;Xu et al, 2021;Zhang et al, 2021). Therefore, we investigated whether MEMC could activate Nrf2 and found that the level of p-Nrf2 expression indicating that Nrf2 was activated was clearly upregulated by H 2 O 2 in MEMC-pretreated C2C12 cells.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have indicated that irisin or ginsenoside Rg1 attenuates AKI in septic mice through anti-ferroptosis in renal tubular epithelial cells [39, 116]. Some alkaloids, such as pyrazine alkaloids, isoquinoline alkaloids, pyrimidine alkaloids, tropane alkaloids, carbine alkaloids, organic amine alkaloids, and aporphine alkaloids, originating from various Chinese herbs, are crucial in the treatment of AKI [117]. Scientific evidence has also suggested that inhibiting ATF3 expression and halting ferroptosis in renal proximal tubular epithelial cells are two mechanisms by which low-dose quercetin (10 mg/kg) ameliorates AKI [118].…”
Section: Pharmacological Progress Of Ferroptosis In Kidney Diseasesmentioning
confidence: 99%
“…At present, Chinese medicine has received strong support from the World Health Organization and is included in Chapter 26 of the 11th edition of the Global Medical Program. The renoprotective effects of some Chinese medicinal formulas and metabolites have received widespread attention and have been studied in multiple AKI models, including DI-AKI ( Wang et al, 2019 ; Li and Gong, 2022 ; Rui et al, 2022 ; Zou et al, 2022 ). In this review, whether Chinese meteria medica and their preparations or monomers can improve DI-AKI and their potential mechanisms of action were explored.…”
Section: Introductionmentioning
confidence: 99%